Hubungan Pengalaman Magang Du/Di Dan Perencanaan Karir Dengan Kesiapan Kerja Mahasiswa Pendidikan Akuntansi - Valentina, Adinda Anastasya Febi; Muchsini, Binti (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This study aims to examine: (1) the relationship between internship experience and the job readiness of Accounting Education students; (2) the relationship between students' career planning and the job readiness of Accounting Education students; (3) the relationship between internship experience and career planning with the job readiness of Accounting Education students. The population of this study consists of 143 students and sample of 105 students was selected using the Proportionate Stratified Random Sampling technique. This study employs a descriptive quantitative method. Data on internship experience, career planning, and student job readiness were obtained through questionnaires. The prerequisite tests used were linearity test, normality test, and multicollinearity test. The data analysis techniques used were simple correlation, multiple correlation, and coefficient of determination. The results of the study indicate that (1) there is a relationship between internship experience and the job readiness of Accounting Education students; (2) there is a relationship between students' career planning and the job readiness of Accounting Education students; (3) there is a relationship between internship experience and career planning with the job readiness of Accounting Education students. Therefore, it can be concluded that there is a relationship between internship experience and career planning with students' job readiness. Keywords: Relationship1; internship experience2; career planning3;